Progression from Subjective Cognitive Decline to Mild Cognitive Impairment or Dementia: The Role of Baseline Cognitive Performance - Jester, Dylan J; Vyhnálek, Martin; Andel, Ross; Marková, Hana; Nikolai, Tomás; Laczó, Jan; Matusková, Veronika; Cechová, Katerina; Sheardova, Katerina; Hort, Jakub (Journal of Alzheimer's disease, 2022)
BACKGROUND: Older adults with subjective cognitive decline (SCD) are at an increased risk of progression to mild cognitive impairment (MCI) or dementia. However, few have examined the specific cognitive tests that are associated with progression. OBJECTIVE: This study examined performance on 18 neuropsychological tests among participants with SCD who later progressed to MCI or dementia. METHODS: We included 131 participants from the Czech Brain Aging Study that had SCD at baseline. They completed a comprehensive neuropsychological battery including cognitive tests from the Uniform Data Set 2.0 enriched by the verbal memory test Rey Auditory Verbal Learning Test (RAVLT) and Rey-Osterrieth Complex Figure Test (ROCFT). RESULTS: Fifty-five participants progressed: 53% to non-amnestic MCI (naMCI), 44% to amnestic MCI (aMCI), and 4% to dementia. Scoring one SD below the mean at baseline on the RAVLT 1 and RAVLT 1-5 was associated with 133% (RAVLT 1; HR: 2.33 [1.50, 3.62]) and 122% (RAVLT 1-5; HR: 2.22 [1.55, 3.16]) greater risk of progression to MCI or dementia over 3.84 years on average. Worse performance on the RAVLT 5, RAVLT 1-5, RAVLT 30, and ROCFT-Recall was associated with progression to aMCI whereas worse performance on the RAVLT 1, TMT B, and Boston Naming Test was associated with progression to naMCI. CONCLUSION: At baseline, lower verbal memory performance was most strongly associated with progression to aMCI whereas lower executive or language performance was most strongly associated with progression to naMCI.
Keywords: kognitivní dysfunkce; Neuropsychological Tests; neuropsychologické testy; testy paměti a učení; Dementia; kognice; Aged; lidé; Memory and Learning Tests; senioři; Cognitive Dysfunction; Humans; demence; Cognition